Pengaruh penggunaan metode Cooperative Integrated Reading and Composition (CIRC) terhadap keterampilan literasi informasi ditinjau dari hasil belajar sejarah siswa (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
Suspendisse eu nibh est. Phasellus ultrices cursus justo, non efficitur risus euismod sed.. This research was motivated by the low information literacy skills of students. The CIRC method is used in the experimental class by dividing students into small groups, which then each finding, processing, and presenting information, as well as making answers to problems. The method used in this research is a quasi experimental method with one group time series design. The research was conducted at SMA Negeri 9 Bandung. The instrument used to obtain data in the study was a written test in the form of multiple choice questions and a questionnaire. Based on the data obtained from the results of the calculation of the hypothesis test, the Sig. 0.004
Keywords: Information Literacy Skills; Cooperative Integrated Reading and Composition (CIRC) Method; Learning Outcomes